Busy beavers - Brownell, M. Barbara ([Washington, D.C.] : National Geographic Society, 1988)
Photographs and text introduce the physical characteristics and habits of the beaver.
Bibliography: p. [34].
Keywords: Beavers -- Juvenile literature; Beavers